Inelastic X-Ray Scattering and X-Ray Powder Diffraction Applications - Cunsolo, Alessandro; Franco, Margareth K. K. D.; Yokaichiya, Fabiano (IntechOpen, 2020)
This book illustrates a few exemplary scientific topics addressed through the use of two complementary x-ray scattering techniques: inelastic x-ray scattering and x-ray powder diffraction. These scattering methods are the focus of the two main sections of this book. These sections are subdivided into chapters discussing specific applications. The general aim of this volume is providing a concise overview of the opportunities disclosed by these two experimental methods, providing some guidance for scientists picking up this field and, hopefully, inspiring more mature scientists towards the achievement of new advances in this area.